Cyclic performance of in-plane shear cross-laminated timber panel-to-panel surface spline connections. (1st September 2020) - Taylor, Bradly; Barbosa, Andre R.; Sinha, Arijit
Highlights: Twenty in-plane shear tests on CLT surface spline connections were performed. Splines were constructed using nails and three different screw spacings. Nail spline connections were more ductile than the screw connections. An engineering performance model for the CLT splines is presented. Abstract: Cross-laminated timber (CLT) panels have been used as structural diaphragm elements that form the primary lateral force-resisting system in mass-timber buildings. To better understand the overall performance of CLT diaphragms, an experimental program including monotonic and cyclic in-plane shear panel-to-panel spline connections tests was conducted. The spline connections were constructed using nails and screws with different spacings. Experimental results from the testing program allow for characterization of the performance of the connection systems in terms of elastic stiffness, strength, and ductility. Based on the results of this specific testing program, nailed spline connections displayed similar performance in terms of stiffness and strength and were more 58.7% more ductile than the screw connections, which is partly explained by the larger overstrength factors observed for the screw connections. A simplified performance model is presented to aid designers in determining the elastic, inelastic, and post-peak force parameters of the various spline connections tested.